Does Playground Improvement Increase Physical Activity among Children? A Quasi-Experimental Study of a Natural Experiment. (13th June 2013) - Bohn-Goldbaum, Erika E.; Phongsavan, Philayrath; Merom, Dafna; Rogers, Kris; Kamalesh, Venugopal; Bauman, Adrian E.
Abstract : Outdoor recreational spaces have the potential to increase physical activity. This study used a quasi-experimental evaluation design to determine how a playground renovation impacts usage and physical activity of children and whether the visitations correlate with children's physical activity levels and parental impressions of the playground. Observational data and intercept interviews were collected simultaneously on park use and park-based activity among playground visitors at pre- and postrenovation at an intervention and a comparison park during three 2-hour periods each day over two weeks. No detectable difference in use between parks was observed at followup. In the intervention park, attendance increased among boys, but decreased among girls although this (nonsignificant) decline was less marked than in the comparison park. Following renovation, there was no detectable difference between parks in the number of children engaged in MVPA (interaction between park and time: P = 0.73 ). At the intervention park, there was a significant decline in girls engaging in MVPA at followup (P = 0.04 ). Usage was correlated with parental/carer perceptions of playground features but not with physical activity levels. Renovations have limited the potential to increase physical activity until factors influencing usage and physical activity behavior are better understood.